Effect of drought and salinity stress on Calcium oxalate crystals of Portulacaria afra. (L.) Jacq. - Ruchira Javkar; Anil Avhad (Journal of Stress Physiology & Biochemistry, 2023)
Oxalic acid (C2H2O4) and Calcium (Ca2+) react to form the salt Calcium oxalate (CaOx), which crystallises into a variety of topologically diverse crystals. CaOx crystals have been found in at least 215 plant groups, which corresponds to numerous species. Crystals can be found in vascular, epidermal, ground, and other tissues in addition to roots, stems, leaves, flowers, fruits, and seeds. They develop in crystal idioblasts, specialised cells, in their vacuoles. According to recent studies, CaOx crystals are in fact useful tools that are crucial, especially in stressful conditions. As plants lack an excretory system, the Ca component regulates the cytosolic concentration levels and immobilises excess amounts of this element. Oxalates operate as a dynamic carbon store and set off an alert during photosynthesis, which results in the production of CO2. The article aims to provide readers with a greater understanding of Portulacaria afra's CaOx crystals and the projected crystal disintegration that would liberate carbon and supply the photosynthetic cycles with it as defence against salinity and drought stress.